Asuhan Kebidanan Continuity of Care Ny. R Umur 40 Tahun di PKM X dengan Kehamilan Anemia Ringan - Alifia Jumeisya Setiawan; Luvi Dian Afriyani (Universitas Ngudi Waluyo, 2024)
Continuity of care is the provision of obstetric care starting from pregnancy, childbirth, postpartum, neonate to deciding to use family planning. This aims to help, monitor, and detect the possibility of complications that accompany the mother and baby from pregnancy to the use of birth control. The midwifery care method at PKM X is through home visits by providing counseling according to the needs of mothers. The obstetric care given to Mrs.